English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

y=2x^2+8x+18. First factor out your 2.
y=2(x^2+4x+9). Then complete the square.
y=2(x^2+4x+4+9-4). Then remove unnecessary elements (The 9 and -4.
y=2(x^2+4x+4)+10. Factor the trinomial.
y=2(x+2)^2+10
And, viola!

2007-01-18 07:58:52 · answer #1 · answered by πρ 6 · 1 0

First factor out 2, giving you y=2(x^2+4x+9).
Now, (4/2)^2=4.
So, knowing this y=2(x^2+4x+4+5).
Or y=2(x^2+4x+4)+(2*5).
So, we need to subtract 2*5=10 from both sides, giving us
y-10=2(x^2+4x+4), or y-10=2(x+2)^2.

2007-01-18 08:04:17 · answer #2 · answered by yljacktt 5 · 0 0

fedest.com, questions and answers